Similarity but not equivalence: Ecological niche comparison between sandflies from the Pleistocene and future scenarios in Central and South America (2023)
Sandfly species (Diptera: Psychodidae) are suspected or proven vectors of Leishmania spp. in the American region. Understanding niche conservatism (NC) in insect vectors allows an understanding of constraints on adaptive responses, and thus implications for disease ecology. Therefore, in this study, the authors evaluated NC in three vector species of leishmaniasis (Lutzomyia gomezi, Psathyromyia shannoni and Pintomyia ovallesi) in Central and South America. For this, the authors performed niche identity and similarity testing through paired comparisons in ENMTools and niche overlap in Niche Analyst. The authors found that species niches were more similar to each other than if the points had been randomly extracted, and they also found extensive similarity between Pa. shannoni and Lu. gomezi niches and in Pa. shannoni niches over different timescales. The authors suggest Pa. shannoni as a priority species due to fundamental niche similarity with phylogenetically related species and also its extensive evolutionary history and ecological plasticity that could affect the emergence and resurgence of leishmaniasis in areas endemic by this vector.